Modeling, Simulation and Experimental Validation of a Solar Dryer for Agro-Products with Thermal Energy Storage System - Reyes-Salinas, A; Vasquez-Fajardo, J; Pailahueque-Barahona, N (Elsevier Ltd, 2019)
This paper presents a dynamic model of a solar dryer for agro-products with thermal energy storage system, using paraffin wax as phase change material. The mathematical model of the dryer was separated in three stages: a solar panel, a solar accumulator and a drying chamber. The system of equations was solved using numerical integration. The models were validated with experimental data reported in previous studies on the drying of kiwifruit and mushrooms. Temperatures was measured at the outlet of the solar panel and solar accumulator, solid moisture content and air humidity were measured at the inlet and outlet of the drying chamber. Based on fit evaluations R2 and RMSE, the model accurately predicts temperature and humidity of the drying air, temperature and moisture of the product, behavior of the heat transfer and drying parameters and time variable climatic conditions ambient temperature, air humidity, and solar radiation. © 2019 Elsevier Ltd